2020
DOI: 10.1080/13607863.2020.1727852
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, motivators and facilitators of physical activity in people with dementia and their family carers in England: dyadic interviews

Abstract: Introduction: Physical activity may have a number of physical and mental health benefits for people with dementia and their carers. However, there is limited evidence about factors that influence physical activity participation in these groups. This study therefore looks at the barriers, facilitators and motivators of physical activity in people with dementia, from both the perspective of the person with dementia and their carer. Method: Thirty participants (15 sets of community-dwelling people with dementia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Given that we analysed cross-sectional data, we cannot make any conclusions about the causal relationship. There is evidence for both the functional health benefits of LTPA [45,46] and the limitations of LTPA due to functional impairment [16]. Furthermore, depression may mediate the relationship between LTPA and functional impairment [52,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that we analysed cross-sectional data, we cannot make any conclusions about the causal relationship. There is evidence for both the functional health benefits of LTPA [45,46] and the limitations of LTPA due to functional impairment [16]. Furthermore, depression may mediate the relationship between LTPA and functional impairment [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review van Alphen, Hortobagyi [15] showed that difficulties with guidance and organization of physical activities by caregivers is a prominent barrier to physical activity. Farina, Williams [16] reported, based on a qualitative study, that physical activity of persons with dementia can be promoted by supporting caregivers in general and by facilitating the caregiver's own physical activity. However, previous findings were mostly based on small samples and did not account for sex-specific effects.…”
Section: Introductionmentioning
confidence: 99%
“…Braun and Clarke’s (30) thematic analysis method has been validated to answer a range of research questions (35) and has been used in other recent qualitative descriptive caregiver studies (e.g. 36, 37). Two authors immersed themselves in the data by independently reviewing the data, producing initial codes and grouping these codes to create themes.…”
Section: Methodsmentioning
confidence: 99%
“…which include perception of aging (not wanting to push themselves physically), not wanting to leave their caree alone / leaving them for too long, their caree being unsafe to take part in activities (e.g. bike rides) or unable to participate socially in group activities, health conditions causing pain / risk of falling, feeling tired / lacking energy due to the PA associated with caring, lack of time due to caring role, difficulties in changing routine for their caree, and their own PA being inhibited through supporting the caree being active (29,30). Malthouse et al's (2014) study only involved a small sample of spousal carers of individuals with Alzheimer's disease, so it must be recognised that the barriers to PA for other groups of carers may differ (29).…”
Section: Barriersmentioning
confidence: 99%
“…Malthouse et al's (2014) study only involved a small sample of spousal carers of individuals with Alzheimer's disease, so it must be recognised that the barriers to PA for other groups of carers may differ (29). Farina et al's study included a slightly larger sample, but, again, only considered carers of individuals with dementia (30).…”
Section: Barriersmentioning
confidence: 99%